Assessing the Benefit of a Personalized EHR‐Generated Informed Consent in a Dental School Setting. Issue 8 (1st August 2014) - Valenza, John A.; Taylor, David; Walji, Muhammad F.; Johnson, Craig W.
Abstract : Informed consents are routinely used as an important source of information to help patients make appropriate clinical decisions. However, current standard consent forms may not accomplish their intended purpose due to the variety of patient literacy and experiences and, in the dental school setting, the developing competence of students. The purpose of this pilot study was to test the efficacy of a personalized informed consent generated through an electronic health record (EHR) at one dental school and its role in patient decision making. In the study, a set of informed consents, or SmartConsents, were developed for specific diagnoses and procedures, enhanced with graphics, and delivered through the school's EHR. Fifty patients were recruited in the school's Urgent Care Clinic and divided evenly into two groups: one (control) receiving the standard consent, with the second receiving a SmartConsent . Following treatment, patients were assessed based on demographics, decisional conflict, satisfaction, health literacy, and knowledge. Overall, there were no significant differences in main effects between SmartConsent and standard informed consents for decisional conflict and satisfaction, although significant differences were identified during secondary analysis of satisfaction, gender, and ethnicity. The study also demonstrated the potential for consents to aid the student provider in better communicating with patients.